Reorganization of Federal Science and Technology Activities. (U.S. Congressional Research., 1977)
Compilation, prepared by Dorothy M. Bates (CRS), of legislative histories and descriptions of significant reorganizations, proposed and implemented, for the conduct of executive branch scientific and technological policy activities, 1962 through Mar. 31, 1977.